Mangrove Plants Use As Medicine In Gedangan Village, Purwodadi District, Purworejo Regency, Central Java Province - Slamet Mardiyanto Rahayu; Sunarto (Jurnal Jamu Indonesia, 2020)
Coastal ecosystems have high plant levels, for example mangroves and seagrasses. Mangrove forest is a type of forest located in tidal areas, especially on protected beaches, lagoons, river estuaries that are inundated and free from inundation at low tide, whose plant communities tolerate salt. Gedangan Village is one of the villages in Purwodadi District, which has mangrove areas in Purworejo Regency. This study aims to determine the types of mangrove plants that are useful the Gedangan Village, Purwodadi District, Purworejo Regency, Central Java as medicinal products. The study was conducted using roaming method in the form of observations or field observations in the mangrove area of Gedangan Village, Purwodadi District, Purworejo Regency, Central Java. Based on the research, there were eight (8) types of mangrove plants that were found as medicinal plants in Gedangan Village, namely Rhizophora mucronata, Sonneratia alba, Calotropis gigantea, Nypa fruticans, Acanthus ilicifolius, Hibiscus tiliaceus, Ipomoea pescaprae, and Wedelia biflora. Traditionally, these mangrove species can be used as a medicine items for beri-beri, hepatitis, ulcers, wounds, diarrhea, fever, antibacterial, anti-inflammatory, dizziness, asthma, bronchitis, dyspepsia, leprosy, tumors, diabetes, stomach ache, toothache, thrush, tuberculosis, muscle aches, and eczema.